An Analysis of the Role of Participation in Sustainable Social Development Neighborhoods Case Study: Neighborhoods of District 8 of Tehran - Maryam rahmani Lashgari; Alireza Estalaji; Azita Rajabi; Majid Vali Shariat Panahi (تحقیقات کاربردی علوم جغرافیایی)
Social sustainability today, as the most important dimension of sustainable development, has an important place in urban planning and its importance in planning is constantly increasing with the increase of social problems and divergence between neighborhoods in terms of performance and participation. Therefore, this requires more research in urban studies. This study was conducted to investigate the role of social participation in the development of social sustainability in neighborhoods. For this purpose, the significance of the significant effect of these two variables has been measured. The research is applied in terms of purpose and descriptive-analytical in terms of method. Data collection was library and field method. The statistical population of the study consists of a group of experts who were selected by the available method of 20 people as the sample size of the study. Data collection tool is a questionnaire based on theoretical foundations and studies conducted on a five-point Likert scale. Data analysis was performed using structural equations with the help of Emus software. The results showed that the social participation of citizens in neighborhoods with a coefficient (beta) of 0.732 has a positive effect on sustainable social development of these neighborhoods and the relationship between these two variables is significant. In other words, sustainable social development will be strengthened by strengthening social participation. And the variables of sense of belonging, satisfaction with the neighborhood, participation in neighborhood activities and trust also have a positive effect on the variables of social participation in neighborhoods.